PEGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA APLIKASI PESAN ANTAR MAKANAN ONLINE (STUDI KASUS MAHASISWA POLITEKNIK LP3I JAKARTA) - Rahayu Tri Utami; Yopy Ratna Dewanti; Setiawan (NIAGARA Scientific Journal, 2022)
Consumer decisions are an approach to solving problems in human activities to buy goods or services to fulfill their wants and needs. Quality and service and price are determinants in terms of consumer decisions in buying food using the Online Food Delivery Service Application. Interpreting the results of research analysis, namely interpreting the hypothesis testing. Although the results of the statistical analysis itself are already a conclusion, they are not adequate without any interpretations associated with problemformulation, interpretation and hypothesis testing. The simultaneous influence betweenService Quality (X1) and Price (X2) variables on Purchase Decisions (Y) is 0.8375 classified as very strong. While the joint contribution (simultaneous) of the variables X1 and X2 to Y = R2 x 100% or 0.8375 x 100% = 70%. While the remaining 30% is determined by other variables. Based on the calculation that the magnitude of the influence between the variables of Service Quality (X1) on Purchase Decisions (Y) which is calculated by thecorrelation coefficient is 0.753 or (rx1y = 0.753. This shows a strong influence between Price on Purchase Decisions. While the significant level of one-sided correlation coefficient (1-tailed) of the output (measured by probability) yields a number of 0.00 or 0. Because the probability is far below 0.01 or 0.05, the effect of Service Quality on Purchase Decision is significant.